1995
DOI: 10.1111/j.1432-1033.1995.tb20419.x
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific N‐terminal Auto‐degradation of Human Serum Albumin

Abstract: Human serum albumin prepared by blood fractionation for clinical purposes was found to degrade when stored at or above 30°C. Mass spectrometry and N-terminal sequencing of the protein identified degradation corresponding to the loss of the first two residues, aspartic acid and alanine. The reaction was shown to be dependent upon temperature and the N-terminal a-amino group. In addition, comparison with serum albumins derived from other species showed that the instability of the N-terminus was specific to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 14 publications
5
48
0
5
Order By: Relevance
“…Generation of ROS can transiently modify the N-terminal region of albumin and produce an increase in IMA levels (23,24). Some authors (24,25) reported that ROS generation in vitro causes structural changes in a synthetic N-terminus tetrapeptide, an octapeptide, and human albumin with loss of Co 21 binding capacity. High or low albumin concentrations may affect IMA testing, producing lower or higher values, respectively, even within the reference interval.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of ROS can transiently modify the N-terminal region of albumin and produce an increase in IMA levels (23,24). Some authors (24,25) reported that ROS generation in vitro causes structural changes in a synthetic N-terminus tetrapeptide, an octapeptide, and human albumin with loss of Co 21 binding capacity. High or low albumin concentrations may affect IMA testing, producing lower or higher values, respectively, even within the reference interval.…”
Section: Discussionmentioning
confidence: 99%
“…According to Marx G and Chevion M [29], albumin, the predominant protein in circulation, undergoes site-specific modification in N-terminus, especially of the N AspAla-His-Lys sequence during overproduction of ROS resulting from conditions related to ischemia, hypoxia, acidosis, free radicals [30][31][32][33] is unable to bind transition metals like, cobalt [31]. This is the basic mechanism to detect the ischemia modified albumin.…”
Section: Discussionmentioning
confidence: 99%
“…231 It is also known that the N-terminal portion of human serum albumin is susceptible to biochemical degradation and is less stable than the albumin of other species. 232 Ischaemia-modified albumin (IMA) is a form of human serum albumin in which the N-terminal amino acids have been affected so that they are unable to bind transition metals. Measurement of IMA is with the albumin cobalt-binding (ACB ® , Ischemia Technologies, Denver, CO) test.…”
Section: Ischaemia-modified Albuminmentioning
confidence: 99%